Efforts to Increase Mothers' Knowledge About Postpartum Blues - Rahmawati, Rahmawati; Mujahid, Edy Husnul; Kusnan, Adius; Saida, Saida; Sukurni, Sukurni; Indriastuti, Diah (Society : Jurnal Pengabdian Masyarakat, 2025)
Postpartum blues, also known as baby blues, is a common emotional condition experienced by mothers after childbirth. If not properly addressed, it can significantly affect the mother's mental health and overall family well-being. Limited awareness of postpartum blues, particularly in Nambo Village, Kendari City, has driven the implementation of this community service initiative. The objective was to improve pregnant women’s understanding of the symptoms, causes, as well as strategies to manage and prevent postpartum blues.The activity was conducted on Saturday, November 2, 2024, at the Nambo Village Hall, involving a team of lecturers from the Faculty of Medicine, Halu Oleo University. The methods used included interactive counseling, group discussions, simulations, and the distribution of educational materials. A total of 25 pregnant women participated in the program. Evaluation was carried out using pre-test and post-test assessments to measure the increase in participants' knowledge.Results indicated an 85% improvement in participants' understanding after the counseling session. This initiative successfully raised awareness and enhanced the understanding of pregnant women about postpartum blues, while also encouraging openness in discussing mental health issues. The intervention demonstrated that community-based education can serve as a strategic approach to improving maternal and family health quality. Moving forward, follow-up programs are needed to strengthen and sustain the positive impacts achieved through this activity.